Brain Pathogenesis and Potential Therapeutic Strategies in Myotonic Dystrophy Type 1 - Liu, Jie; Guo, Zhen-Ni; Yan, Xiu-Li; Yang, Yi; Huang, Shuo (Frontiers in Aging Neuroscience, 2021)
Myotonic dystrophy type 1 (DM1) is the most common muscular dystrophy that affects multiple systems including the muscle and heart. The mutant CTG expansion at the 3′-UTR of the DMPK gene causes the expression of toxic RNA that aggregate as nuclear foci. The foci then interfere with RNA-binding proteins, affecting hundreds of mis-spliced effector genes, leading to aberrant alternative splicing and loss of effector gene product functions, ultimately resulting in systemic disorders. In recent years, increasing clinical, imaging, and pathological evidence have indicated that DM1, though to a lesser extent, could also be recognized as true brain diseases, with more and more researchers dedicating to develop novel therapeutic tools dealing with it. In this review, we summarize the current advances in the pathogenesis and pathology of central nervous system (CNS) deficits in DM1, intervention measures currently being investigated are also highlighted, aiming to promote novel and cutting-edge therapeutic investigations.